The What, the When, and the Whether of Intentional Action in the Brain: A Meta-Analytical Review - Zapparoli, Laura; Seghezzi, Silvia; Paulesu, Eraldo (Frontiers in Human Neuroscience, 2017)
In an attempt of fractionating the concept of intentionality in discrete subcomponents, Brass and Haggard (2008) proposed their What, When and Whether model (www-model) which postulates that the content, the timing and the possibility of generating an action can be partially independent both at the cognitive level and at the level of their neural implementation. The original proposal was based on a limited number of studies, which were reviewed with a discursive approach. To assess whether the model stands in front of the more recently published data, we performed a systematic review of 15 PET/fMRI studies with a meta-analytic method based on a hierarchical clustering algorithm. HC revealed the existence of a rostro-caudal gradient within the medial prefrontal cortex, with the more anterior regions (the anterior cingulum) involved in more abstract decisions of whether to execute an action and the more posterior ones (the middle cingulum or the SMA) recruited in specifying the content and the timing components of actions. However, in contrast with the original www-model, this dissociation involves also brain regions well outside the median wall of the frontal lobe, in a component specific manner: the supramarginal gyrus for the what component, the pallidum and the thalamus for the when component, the putamen and the insula for the whether component. We then calculated co-activation maps on the three component-specific www clusters of the medial wall of the frontal/limbic lobe: to this end, we used the activation likelihood approach that we applied on the imaging studies on action contained in the BrainMap.org database. This analysis confirmed the main findings of the HC analyses. However, the BrainMap.org data analyses also showed that the aforementioned segregations are generated by paradigms in which subjects act in response to conditional stimuli rather than while driven by their own intentions. We conclude that the available data confirm that the neural underpinnings of intentionality can be fractionated in discrete components that are partially independent. We also suggest that intentionality manifests itself in discrete components through the boosting of general purpose action-related regions specialized for different aspects of action selection and inhibition.